A role for TRPC3 in mammalian testis development - Ming, Zhenhua; Bagheri-Fam, Stefan; Frost, Emily R.; Ryan, Janelle M.; Vining, Brittany; Harley, Vincent R. (Frontiers in Cell and Developmental Biology, 2024)
SOX9 is a key transcription factor for testis determination and development. Mutations in and around the SOX9 gene contribute to Differences/Disorders of Sex Development (DSD). However, a substantial proportion of DSD patients lack a definitive genetic diagnosis. SOX9 target genes are potentially DSD-causative genes, yet only a limited subset of these genes has been investigated during testis development. We hypothesize that SOX9 target genes play an integral role in testis development and could potentially be causative genes in DSD. In this study, we describe a novel testicular target gene of SOX9, Trpc3. Trpc3 exhibits high expression levels in the SOX9-expressing male Sertoli cells compared to female granulosa cells in mouse fetal gonads between embryonic day 11.5 (E11.5) and E13.5. In XY Sox9 knockout gonads, Trpc3 expression is markedly downregulated. Moreover, culture of E11.5 XY mouse gonads with TRPC3 inhibitor Pyr3 resulted in decreased germ cell numbers caused by reduced germ cell proliferation. Trpc3 is also expressed in endothelial cells and Pyr3-treated E11.5 XY mouse gonads showed a loss of the coelomic blood vessel due to increased apoptosis of endothelial cells. In the human testicular cell line NT2/D1, TRPC3 promotes cell proliferation and controls cell morphology, as observed by xCELLigence and HoloMonitor real-time analysis. In summary, our study suggests that SOX9 positively regulates Trpc3 in mouse testes and TRPC3 may mediate SOX9 function during Sertoli, germ and endothelial cell development.